Методика оценки эффективности использования в системе электроснабжения полупроводниковых преобразователей постоянного напряжения - Поляков, М.А.; Ларионова, Т.Ю. (Електротехніка і електромеханіка, 2016)
Разработана методика оценки эффективности использования силового полупроводникового преобразователя постоянного напряжения в системе электроснабжения. Методика включает выявление множества внешних факторов,
влияющих на эффективность использование преобразователя; разработку модели оценки эффективности как функции внешних факторов; выбор варианта использования преобразователя; установление коэффициентов корреляции
между значениями внешних факторов; определение значений КПД преобразователя; нахождение распределения КПД
преобразователя. Применение предложенной методики проиллюстрировано на примере синхронного промежуточного вольтодобавочного преобразователя постоянного напряжения. Для этой цели выполнено статистическое моделирование преобразователя этого типа при стохастичном изменении входного напряжения. Розроблено методику оцінки ефективності використання силового напівпровідникового перетворювача постійної
напруги в системі електропостачання. Методика включає виявлення множини зовнішніх чинників, що впливають на
ефективність використання перетворювача; розробку моделі оцінки ефективності як функції зовнішніх чинників;
вибір варіанта використання перетворювача; встановлення коефіцієнтів кореляції між значеннями зовнішніх чинників; визначення значень ККД перетворювача; знаходження розподілу ККД перетворювача. Застосування запропонованої методики проілюстровано на прикладі синхронного проміжного вольтододаткового перетворювача постійної
напруги. Для цієї мети виконано статистичне моделювання перетворювача цього типу при стохастичній зміні вхідної напруги. Purpose. To specify efficiency evaluation of the DС-DC power
semiconductor converter application in the power-supply system.
Methodology. We have chosen application version of converter
and then used the statistical modeling of DC-DC converter for its
efficiency evaluation at varied input voltage according to proposed technique. We have compared the simulated result with the
data presented in reference literature. Results. We have proposed
the efficiency evaluation technique of converter application. Proposed technique includes detection of external factors influenced
on the converter efficiency; development of efficiency evaluation
models; selecting application version of converter; determination
of the correlation coefficients between the values of external factors; definition of the converter efficiency; obtaining of the converter efficiency distribution. Originality. For the first time, we
have developed the evaluation technique of converter efficiency
corrected for application version of converter. Practical value.
Presented in the study results could be useful for specialists in
semiconductor equipment, electrical facilities and systems.